Understanding the interplay between immune response and virus evolution - Jagtap, Suraj; advised by Roy, Rahul (Bangalore: Indian Institute of Science, 2023)
RNA viruses are the underlying cause of many human diseases, including the common cold, influenza, dengue fever, and COVID-19. Their ability to evolve rapidly makes them challenging to tackle, resulting in public health threats. A well-known driver of virus evolution is the immune selection pressure, yet for many viruses, how it affects viral evolution remains poorly understood. How RNA viruses interact and evolve under the influence of the human immune system can help us develop effective treatments and better vaccines. At the same time, studying the immune response to viruses and their antigens can provide insights into how the human body develops immunity and how it can be boosted to fight infections. In the first part of the thesis, we studied the diversity and evolution of the dengue virus (DENV) in India. Dengue is a mosquito-borne disease with four closely related virus serotypes (DENV1-4). About one-third of the global dengue cases are estimated to be from India. Yet we have a limited understanding of the dengue virus diversity and evolution in the country. Further, cross-reacting dengue antibodies from a prior infection from one serotype can protect or enhance infection from other serotypes. This can force the emergence of new dengue variants that find ways to escape the immune action and/or take advantage of it. In endemic countries like India, high rates of previous dengue infection can, hence drive the evolution of dengue serotypes in complex ways. We sequenced 118 whole genomes from dengue patients collected over 7 years from four major cities across India. We combined them with all dengue sequences available fromIndia and compared them with the global strains of dengue. We examined the spatio-temporal dynamics of India-specific genotypes, their evolutionary relationship with global and local dengue virus strains, interserotype dynamics and their divergence from the vaccine strains. Our analysis highlights the co-circulation of all DENV serotypes in India with cyclical outbreaks every 3-4 years. In South India, where seropositivity is very high, the envelope (E) protein displays strong signatures of evolution under immune selection. Apart from drifting away from its ancestors and other contemporary serotypes, we find evidence for recurring interserotype convergence, suggesting selection via antibody-dependent enhancement. We identify the emergence of the highly divergent DENV4-Id lineage in South India, which has acquired half of its E gene mutations in the antigenic sites. Moreover, the DENV4-Id is drifting towards DENV1 and DENV3 clades, suggesting the role of cross-reactive antibodies in its evolution. Our study shows how high incidence and pre-existing population immunity might shape dengue virus evolution in India. In the second part of my thesis, I examine how antibody response to the SARS-CoV-2 virus evolves after COVISHIELD vaccination/ natural infection. We developed in-house ELISA assays to quantify the antibody levels (IgG and IgA) against the spike trimer, RBD and nucleocapsid proteins. Both IgG and IgA antibodies reached peak levels within 15-21 days of infection. Similarly, we observed an increase in antibody titers within the first 14 days post-COVISHIELD vaccination. The antibody levels waned over three months but were boosted after the second dose of the vaccine. We observed very high antibody titers in the case of COVID-19 recovered individuals with the first vaccination shot. The exposure due to infection also induces the IgA response, which is not mounted by vaccination alone. We found that although the antibody levels are lower, single vaccination can help reduce disease severity during breakthrough infections.
includes bibliographical references and index
PhD; 2023; Chemical Engineering
Keywords: Dengue evolution; phylogenetics; immune system